PROPOSED STRATEGY OF BIODIESEL FUEL POLICY IN THE COAL MINING INDUSTRY - A CASE STUDY OF PT. BERAU COAL - I H Bunga Naen, Alfons
Indonesian Government has mandated the use of biodiesel in various sectors. Starting in September 2018, the use of biodiesel in Indonesia, and also at PT. Berau Coal has reached a blended rate of 30% (B30). The purpose of this final project is to formulate actions that must be taken by PT. Berau Coal to face the mandate of using biodiesel. During biodiesel implementation, PT. Berau Coal is experiencing two business issues related to biodiesel: the increase of fuel filter replacement cost and fuel cost increase. Based on the root cause analysis, there are three root causes of the problems, namely the biodiesel's content/specification, the readiness of the Company's infrastructure in terms of the fuel filtration system, and weak administrative controls resulting from differences in fuel quality standards between regulations and industrial needs. Business issues will be solved by implementing several projects/activities where all the project/activities will be designed to cover all the parties from the strategic level to the operational level to achieve the maximum value (the combination of Project Drive Change and Supply Chain Management Concept). The business solution consists of several projects from the upstream to downstream sides, including Government, Suppliers, PT. Berau Coal and Mining Contractors. Internal improvements on the downstream side by PT. Berau Coal will be carried out by improving the fuel filtration system. Improvement from the external side involves the Government and suppliers. The Government is expected to make adjustments to regulations related to fuel quality standards and provide incentives for the mining industry, which contributes significantly to the implementation of the mandatory biodiesel. Meanwhile, for the fuel quality control process, changes will be made to the fuel sale and purchase contract. The baseline of feasibility analysis regarding improvement projects at the downstream side involving PT. Berau Coal and Mining Contractor are shown good results with Net Present Value (NPV) are IDR 2.392.660.760,-, Profitability Index (PI) is 1.67, 37% of Internal Rate of Return (IRR), and 26 months of payback period (PBP). The feasibility parameter can be optimized if the improvements are also covering the parties outside, including Government and suppliers. By improve all the fuel supply chain, the parameters arise as follow : NPV = IDR 3.254.987.168,-, Profitability Index = 1.92, IRR = 45% and PBP = 23 months.